Municipal Ownership of Street Railways in Detroit - Moore, Charles (Quarterly Journal of Economics, 1899)
Municipal Ownership of Street Railways in Detroit Get access Charles Moore Charles Moore Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 13, Issue 4, July 1899, Pages 453–459, https://doi.org/10.2307/1883648 Published: 01 July 1899